The Effect of the RME Learning Model on Problem-Solving Ability of Grade X Students at SMK Negeri 2 Kediri - Devi, Faradilla Candra; Katminingsih, Yuni; Widodo, Suryo (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the effect of the Realistic Mathematics Education (RME) learning paradigm on the problem-solving abilities of tenth-grade students at SMK Negeri 2 Kediri. The study uses a quantitative approach. Participants in this research were students from class X Hospitality 2 at SMK Negeri 2 Kediri. Students’ cognitive abilities acquired during the formal operational stage were considered when selecting the population. Each class was randomly sampled under the assumption that all classes were homogeneous. Not all students occupied seats in class X due to the study being conducted in a school environment, where researchers were required to comply with institutional regulations. Based on the research results, the experimental class scored 63.29 on the pre-test before receiving the Realistic Mathematics Education model and 86.32 on the post-test after being treated with the RME learning model. The problem-solving abilities of tenth-grade students at SMK Negeri 2 Kediri can be influenced by the application of the RME learning paradigm.